Challenges in Restoration of Livelihood Faced by Project-Affected Persons - Godiyal, Chetna; Saluja, Mahima (Calibrating Urban Livability in the Global South, 2024)
Development is the indicator of progress and growth, in the physical, economic, environmental, social and demographic components, which is achieved by procurement of land for the establishment of these projects. The process of land acquisition leads to the displacement of the native population, which results in the Resettlement and Rehabilitation (R&R) of the affected people. While the main aim of these projects is to target economic efficiency and enhance the livability of an urban area, the plight of project-affected people is not catered to efficiently. In recent years R&R for project-affected persons has been a vital and sensitive issue that dwells impoverishment risks like loss of livelihood, homelessness, destruction of social cohesion etc. The paper aims to study the impact on the livability of project-affected persons, post-implementation of infrastructure projects. The focus of the research relies on case examples from the global south, that cater to the livelihood restoration for project-affected populations and the cause and effect of the approaches practiced to formulate the framework. To achieve the desired objectives, a qualitative research approach was used to analyze the case example of Yamuna-Expressway Way in Uttar Pradesh. Under this project, approximately 5000 hectares of land has been acquired, for which the compensatory framework did not pan out as the asset value depleted. Due to this the project-affected people (PAP) were compelled to use the monetary compensation to incur better livelihood opportunities. The study concludes by identifying a gap in the implementation of the Livelihood Restoration Plan (LRP) for project-affected people and formulation of a conceptual framework for LRP. LRP is essential for sustainable economic planning and an important indicator of successful rehabilitation and resettlement action plans.